2015
DOI: 10.1515/amm-2015-0229
|View full text |Cite
|
Sign up to set email alerts
|

Study Of Rust Preventive Characteristics Of Rust Preventive Oil From Polarization Curve Measurement

Abstract: Fe-Cu-C sintered steels are widely used as powder materials, because of its small volumetric shrinkage. However, Cu, which acts as cathode enhance formation of rust Fe 2 O 3 ·xH 2 O during fabrication. To prevent formation of Fe 2 O 3 ·xH 2 O rust preventive oils are widely used. High viscosity of those rust preventive oils decrease workability. While, low viscosity degrade rust preventive performance. Therefore, it is necessary to develop new rust preventive oils with contradictory properties of low viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
0
0
Order By: Relevance
“…Iwashima in our laboratory also reported similar results. 11,12) Present experiments were also in good agreement with theirs. At the beginning, surfactant molecules contained in a rust preventive oil applied to a specimen surface are aligned along the interface between a water screen and a rust preventive oil.…”
Section: Methodssupporting
confidence: 87%
“…Iwashima in our laboratory also reported similar results. 11,12) Present experiments were also in good agreement with theirs. At the beginning, surfactant molecules contained in a rust preventive oil applied to a specimen surface are aligned along the interface between a water screen and a rust preventive oil.…”
Section: Methodssupporting
confidence: 87%
“…In the past, measurement results using various rust preventive oils in the study of sintered Fe/Cu-based steels have been reported [6]. In addition, Nagase and his colleagues reported the results of water semi-immersion rust prevention test etc.…”
Section: Introductionmentioning
confidence: 99%